Gender related differences in development of certain motor abilities in talented youth table tennis players - Kondric, M.; Nikolic, I.; Furjan-Mandic, G.; Munivrana, G.; Ochiana, N.; Matjašic, T. (Science and Racket Sports VI, 2019)
Table tennis is a complex polystructural game, where a variety of motor abilities determine success. Our research stems from the assumption that these abilities, which undoubtedly play an important role in competitive level table tennis game, develop with age and training, but at different rates between genders. We applied 11 motor tests of power, flexibility, coordination, speed and endurance to a sample of 76 promising Slovenian table tennis players (two groups with average age 12.2 years and 14.8 years, respectively). The younger age group was composed of 29 boys (60.4%) and 19 girls (39.6%) and the older was composed of 17 (60.7%) boys and 11 (39.3%) girls. The data were gathered during regular testing at the Faculty of Sport in Ljubljana in the years 2014 and 2017. Gender and age differences, as well as potential gender-age interactions were tested using two-way analysis of variance. The results provide a more complex picture than the initial assumption. In speed and power, which are central to table tennis, the results, as expected, improved with age and were on average better in boys than in girls. However, regarding flexibility, which is in general superior in the older group, the girls are on average superior to the boys. The overall improvement in coordination with age is smaller, with a notable interaction effect in the sense of marked improvement in boys and stagnation in girls. Basic endurance is the only ability that appears to decline from age 12 to age 15, whereby the trend is more pronounced in girls.